Quality of Life from a Transhumanist Perspective - Plašienková, Zlatica; Farbák, Martin; Smolková, Eva (Studia Ecologiae et Bioethicae, 2022)
The issue of quality of life has been a subject of major interest in the course of history, even though it was originally related to a specific philosophical question of a good life. Nowadays, the quality-of-life issue represents a more complex term, related to a lot of aspects that make human life good, valuable and meaningful. In this article, the authors aim to reflect on the new role of transhumanism, which is promoting a radical scientific and technological enhancement of humans. In its promising visions, the level of quality of human life should be supposedly increased to an almost ideal state for all people. Initially, the authors deal with the issue of the quality of human life concerning individual preferences and social solutions, and they proceed with their beliefs based on the assumption that the guarantor of the life of citizens is the state government. Later on, the authors of the article focus on the given issue relating to transhumanist positions. They critically analyse the transhumanist absolutization of technology as the primary tool for achieving a good human life, whilst overlooking the ethical context of the issue. The authors express their positive standpoint towards human progress and enhancement (especially in medicine), but they recognise a possible risk of dehumanisation. If the transhumanist visions are to be carried out by prioritizing the progress itself before the actual humans, there are deep ethical questions that should be answered.